Monolayer MoS2 Fabricated by In Situ Construction of Interlayer Electrostatic Repulsion Enables Ultrafast Ion Transport in Lithium-Ion Batteries - Han, Meisheng; Mu, Yongbiao; Guo, Jincong; Wei, Lei; Zeng, Lin; Zhao, Tianshou (Nano-Micro Letters, 2023)
High theoretical capacity and unique layered structures make MoS2 a promising lithium-ion battery anode material. However, the anisotropic ion transport in layered structures and the poor intrinsic conductivity of MoS2 lead to unacceptable ion transport capability. Here, we propose in-situ construction of interlayer electrostatic repulsion caused by Co2+ substituting Mo4+ between MoS2 layers, which can break the limitation of interlayer van der Waals forces to fabricate monolayer MoS2, thus establishing isotropic ion transport paths. Simultaneously, the doped Co atoms change the electronic structure of monolayer MoS2, thus improving its intrinsic conductivity. Importantly, the doped Co atoms can be converted into Co nanoparticles to create a space charge region to accelerate ion transport. Hence, the Co-doped monolayer MoS2 shows ultrafast lithium ion transport capability in half/full cells. This work presents a novel route for the preparation of monolayer MoS2 and demonstrates its potential for application in fast-charging lithium-ion batteries. Highlights: 1 In-situ construction of electrostatic repulsion between MoS2 interlayers is first proposed to successfully prepare Co-doped monolayer MoS2 under high vapor pressure. 2 The doped Co atoms radically decrease bandgap and lithium ion diffusion energy barrier of monolayer MoS2 and can be transformed into ultrasmall Co nanoparticles (~2 nm) to induce strong surface-capacitance effect during conversion reaction. 3 The Co doped monolayer MoS2 shows ultrafast ion transport capability along with ultrahigh capacity and outstanding cycling stability as lithium-ion-battery anodes.